Oxygen Embolism During Surgical Lavage of Chronic Osteomyelitis of Femur with Hydrogen Peroxide - Rai, Rem Kumar; Joshi, Amit; Thapa, Bishnu Babu; Magar, Sushil Rana; Sah, Dev Narayan (Nepal Orthopaedic Association Journal, 2014)
Hydrogen peroxide, an over the counter irrigation solution used in infected and dirty wounds, has been reported mainly in the anesthesia literature to have life threatening complications. We report a case of near fatal gas embolism during an orthopedic procedure of irrigating the wound of a 30 year old female with chronic osteomyelitis of the femur using hydrogen peroxide solution. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9528 NOAJ July-December 2013, Vol 3, Issue 2, 41-43